The impact of increased reimbursement rates under the new cooperative medical scheme on the financial burden of tuberculosis patients - Yan-Jiao Xin; Li Xiang; Jun-Nan Jiang; Henry Lucas; Sheng-Lan Tang; Fei Huang (BMC, 2019)
Abstract Background Tuberculosis (TB) is still a major public health problem in China. To scale up TB control, an innovative programme entitled the 'China-Gates Foundation Collaboration on TB Control in China was initiated in 2009. During the second phase of the project, a policy of increased reimbursement rates under the New Cooperative Medical Scheme (NCMS) was implemented. In this paper, we aim to explore how this reform affects the financial burden on TB patients through comparison with baseline data. Methods In two cross-sectional surveys, quantitative data were collected before (January 2010 to December 2012) and after (April 2014 to June 2015) the intervention in the existing NCMS routine data system. Information on all 313 TB inpatients, among which 117 inpatients in the project was collected. Qualitative data collection included 11 focus group discussions. Three main indicators, non-reimbursable expenses rate (NER), effective reimbursement rate (ERR), and out-of-pocket payment (OOP) as a percentage of per capita household income, were used to measure the impact of intervention by comprising post-intervention data with baseline data. The quantitative data were analysed by descriptive analysis and non-parametric tests (Mann-Whitney U test) using SPSS 22.0, and qualitative data were subjected to thematic framework analysis using Nvivo10. Results The nominal reimbursement rates for inpatient care were no less than 80% for services within the package. Total inpatient expenses greatly increased, with an average growth rate of 11.3%. For all TB inpatients, the ERR for inpatient care increased from 52 to 66%. Compared with inpatients outside the project, for inpatients covered by the new policy, the ERR was higher (78%), and OOP showed a sharper decline. In addition, their financial burden decreased significantly. Conclusions Although the nominal reimbursement rates for inpatient care of TB patients greatly increased under the new reimbursement policy, inpatient OOP expenditure was still a major financial problem for patients. Limited diagnosis and treatment options in county general hospitals and inadequate implementation of the new policy resulted in higher inpatient expenditures and limited reimbursement. Comprehensive control models are needed to effectively decrease the financial burden on all TB patients.